Re-doing Rapunzel's hair : viewing subjective cognition in fancifold - Pavlik-Malone, Lisa (Cambridge Scholars Publishing, 2014)
This volume presents an exploration of the role of embodied cognition in creating personal, imaginative renditions of hair, that also distally relate to the symbolic significance of the fairytale character Rapunzel's hair (in terms of physical life, romantic life, spiritual life, and psychic life, respectively). Integral to this relation, is the author's idea of ""fancifold"", which is a quality or state of the imagination that can produce unique neuropsychological elements of enchantment and d ...